PEMBUATAN KOMPOSIT Fe3O4-AMPAS KOPI SEBAGAI ADSORBEN METHYLENE BLUE - Ummi Nor Hidayah; Teguh Wirawan; Soerja Koesnarpadi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Synthesis of Fe3O4-coffee grounds as an adsorbent for methylene blue has been carried out. This study aims to determine the optimum contact time, optimum pH and maximum adsorption capacity and to determine the type of adsorption isotherm on methylene blue adsorption using Fe3O4-coffee grounds composite. This research method was carried out experimentally. The first step was the synthesis of the Fe3O4-coffee grounds composite using the coprecipitation method with a mass ratio of FeCl3.6H2O: (NH4)2Fe(SO4)2.6H2O: Coffee ground (2:2:7). The next step is to determine the optimum contact time, optimum pH and maximum adsorption capacity. The concentration of methylene blue was analyzed using a UV-Vis Spectrophotometer. The results obtained for determining the optimum contact time is 20 minutes with the optimum pH at pH 8 and has a maximum adsorption capacity of 79.85 mg/g. The type of adsorption isotherm follows the Langmuir adsorption isotherm. Keywords: Fe3O4-Coffee Grounds Composite, Adsorption, Methylene blue